DOI: 10.11606/d.75.2013.tde-04042013-151955
|View full text |Cite
|
Sign up to set email alerts
|

Contribuições ao ensino de análise térmica

Abstract: Dedico este trabalho aos meus pais, Marcelo e Vani, aos meus irmãos Gustavo e Giulianna e aos amigos presentes nesta caminhada. RESUMO Considerando a importância crescente das técnicas termoanalíticas na indústria e na pesquisa contemporânea, torna-se necessário apresentá-las de forma adequada aos alunos de cursos de graduação, não apenas de química, mas de ciência dos materiais, física, farmácia, das diversas modalidades de engenharia, entre outros. Por outro lado, pode-se notar que isso raramente acontece, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
2

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
(9 reference statements)
0
0
0
2
Order By: Relevance
“…In TGA/DTG, the peak temperature and the percentage of mass loss in each thermal event depend on the components and the crystal structure of the starch, through which it is possible to draw conclusions regarding the thermal stability of the sample, composition and stability of the compounds, as well as the final product (Denari & Cavalheiro, 2012). In the present study, the thermogravimetric analysis and its derivatives showed that the loss of mass related to moisture, volatiles, starch, glycerin and melamine occurred up to a temperature of approximately 600ºC.…”
Section: Academic Educationmentioning
confidence: 99%
“…In TGA/DTG, the peak temperature and the percentage of mass loss in each thermal event depend on the components and the crystal structure of the starch, through which it is possible to draw conclusions regarding the thermal stability of the sample, composition and stability of the compounds, as well as the final product (Denari & Cavalheiro, 2012). In the present study, the thermogravimetric analysis and its derivatives showed that the loss of mass related to moisture, volatiles, starch, glycerin and melamine occurred up to a temperature of approximately 600ºC.…”
Section: Academic Educationmentioning
confidence: 99%
“…The analytic device consists of a thermobalance (i.e., an instrument that enables continuous weighing of the sample while it is being subjected to varying temperature), an oven, sample support, temperature sensor, oven temperature programmer, and temperature control and recording system (Denari & Cavalheiro 2012).…”
Section: Field Collections and Laboratory Analysismentioning
confidence: 99%
“…Thomasso Grasso ducati 1000/1000 Tommaso Grassi figlio del fu Bertolo, facoltoso cittadino milanese 273 , nel giugno 1449 spese una grossa cifra per acquisire le possessioni di S. Angelo, già ducali 274 , ma nello stesso anno incorse nei bandi della Repubblica Ambrosiana e fu dichiarato ribelle. In marzo era stato accusato dal governo repubblicano di custodire molti beni e pegni di ribelli, in settembre fu bandito 275 Guglielmino da Marliano ducati 400 4.…”
unclassified